FORMULATION AND EVALUATION OF BREAST MILK ETHANOL EXTRACT FRUIT MEAT (Psidium Guajava L.) BY USING VARIATIONS OF EMULGATOR CONCENTRATION - Nuryfa D. Buhang; Gita Puspita; Srimuliani Arbie (Journal of Health, Technology and Science (JHTS), 2021)
Preparations cream is a semisolid dosage forms containing one or more ingredients dissolved or dispersed in the base material which one of the plants that is used as a face cream is guava, because it contains vitamin C which is quite high and has the potential as an excellent antioxidant. This study aims to determine the effect of emulsifier concentration on cream preparations and which formulas show stable results. This research is an experimental study with a posttest only design. The population in this study was guava fruit (Psidium guajava L.) from guava trees in Dulomo Selatan Village, Kota Utara District, Gorontalo. The results showed that in formula I (F1) and formula III (F3) there was a rancid odor, for texture and appearance there had been a change from formula I (F1), namely soft and dense texture and formula II (F2) and formula III (F3). to a soft and fluid texture. The result of measuring the pH of cream preparations in formula 1 (F1) is 7, formula (F2) is 7 and formula (F3) is 7, the test for spreadability of cream preparations in Formula 1 (F1) is 5.25 cm, Formula 2 (F2) 4 .5 cm and Formula 3 (F3) 5.25 cm, the centrifugation test for cream preparations in Formula 1 (F1), Formula 2 (F2) and Formula 3 (F3) separated for 2 hours.